Intervention Programme "SERASI" (Sekolah Ramah Inklusi) in Improving Peer Bystander's Knowledge of Disability and Bullying - Rany Monika Purba; Frieda Mangunson (Inquiry: Jurnal Ilmiah Psikologi, 2020)
This study aims to investigate the effectiveness of SERASI (Sekolah Ramah Inklusi) programme as bullying prevention programme to increase knowledge on the topic of disability and bullying. Improvement in knowledge of disability is expected to increase student acceptance on special needs students. Improvement in knowledge of bullying is expected to increase student’s helping intention as peer bystanders in bullying situation. The SERASI programme consists of disability awareness part and bullying awareness part. Nineteen participants participated for three days in six sessions. Training material covered topics about inclusive education, disabilities, simulations, bullying, role in bullying situations, the importance of bystander roles, and strategies to support bullying victims. This research is a quasi-experimental research with a within-subject design. Measurement carried three times, at before (pre-test), immediately after (post-test), and three months after (post post-test) implementation of SERASI programme. Results of statistical analysis using paired sample t-test showed significant improvement in students' knowledge on topic of disability and bullying after participated in the SERASI programme (M pre-test = 6.68; M post-test = 10.26; t = 6,026; df = 18; p = 0.000). Results of statistical analysis using paired sample t-test also showed students' knowledge on topic of disability and bullying was decreased after three months in the SERASI programme and there were no delayed effects (M post-test = 10.26; M post post-test = 8.11; t = -3.060; df = 18; p = 0.007).